Range of sustainable tourism: a qualitative analysis of the experiences of two communities in Ecuador - Barros Pinto, Freddy Alejandro (2021)
This research conducted a qualitative analysis on the scope of sustainable tourism caused by technical and financial support of international cooperation and NGOs projects in two rural communities in Ecuador: the community of Yunguilla and the community of Oyacachi. It was carried out a documentary compilation and content analysis of the technical financial execution reports, in order to present the experiences obtained through the adoption of sustainable tourism activities. The precise data of the studied texts were codified, then a systematic and interpretative analysis was made to expose the narrative on the scope of sustainable tourism as a guide for development in the communities that are the object of this research. The conclusion is that technical and economic assistance can be two sides of the same coin on the road to sustainability.